Kegiatan Aktualisasi Nilai Pancasila dalam Proses Pembelajaran di Kelas VI SDN Mekarsari Cileunyi Wetan Kabupaten Bandung - Rivaldi Dwi Syahputra; Pramadita Rahmala; Nadia Putri Sahitya; Soffia Hanipah; Sarah Minnurillah Iskandar; Luthfi Haikal Ramadhan; Aditiya Nurrahman; Tuah Harti Ansori; Riva Akmalul Fauzan; Muhammad Farhan Ramadan; Dian Herdiana; Umi Kulsum (Yayasan Daarul Huda Kruengmane, 2025)
The development of information and communication technology, especially the internet, has driven significant changes in the world of education, including in higher education. One form of its application is the use of a Moodle-based e-learning system as a means of supporting the learning process. This study aims to analyze the implementation of Moodle-based e-learning in improving the effectiveness of learning activities at AMIK Stikom Tunas Bangsa Siantar, and compare it with conventional learning methods. The research method used is a combination of qualitative and quantitative, involving 43 third-semester students in the Computer Architecture and Organization course. Data collection techniques include interviews, open and closed questionnaires, observation, documentation, and tests to measure learning outcomes. The research process is carried out in three stages, namely the preparation stage (preparation of RPS and Moodle-based modules), the implementation stage (implementation of synchronous and asynchronous learning), and the reporting stage (analysis of results and preparation of scientific articles). The research results show that implementing Moodle-based e-learning offers several advantages over conventional methods, such as increased interaction between lecturers and students, flexibility in learning time and location, ease of access to materials, and ease of online learning evaluation. Furthermore, e-learning also encourages lecturers to be more creative in developing digital teaching materials and improving their skills in utilizing educational technology. Therefore, it can be concluded that implementing Moodle-based e-learning can improve the quality of the learning process in higher education. The success of its implementation depends not only on the readiness of software, hardware, and internet networks, but also on the lecturers' competence in effectively managing digital learning systems.